Pengaruh Keterlibatan Akademik dan Kesiapan Digital Terhadap Prestasi Akademik Pada Pembelajaran Online - Sulastri Sulastri; Yesi Lintang Priambang (Jurnal Pendidikan Ekonomi (JUPE), 2022)
The aims of this study were to determine: (1) the effect of academic involvement on academic achievement in online learning; and (2) the effect of digital readiness on academic achievement in online learning. The COVID-19 pandemic that occurred in Indonesia had an impact on the education sector. Learning that was previously done face-to-face in class must be replaced with online learning. This research is a quantitative research using multiple regression analysis using SPSS software with a sample of 80 respondents. The sampling technique used is simple random sampling. The results of this study conclude that academic engagement does not have a significant effect on academic achievement in online learning and digital readiness does not have a significant effect on academic achievement in online learning. Therefore, academic engagement and digital readiness are not predictors of academic achievement in online learning.